2021
DOI: 10.1007/s00213-021-05960-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure of cannabinoids with amphetamines and biological, behavioural and health outcomes: a scoping review of animal and human studies

Abstract: Rationale The growing prevalence of psychostimulant (including amphetamine) use and associated health harms, with limited treatment options, present a global challenge. There is an increasing availability and medical applications of cannabinoids, and growing interest in their therapeutic potential for addictive disorders. Objectives The objective of this study is to review available data regarding cannabis/cannabinoid co-use or exposure on amphetamine-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 98 publications
(139 reference statements)
1
9
0
Order By: Relevance
“…Existing evidence suggests that worse neurocognitive performance and higher rates of impairment can result from methamphetamine use (Daldegan-Bueno et al, 2021;Naveed et al, 2022;Reback et al, 2018;Saloner et al, 2020;Scheffler et al, 2022;Watson et al, 2020), and our present results are consistent with these findings. Lifetime methamphetamine use disorder was associated with worse neurocognitive performance and higher rates of NCI, relative to lifetime cannabis use disorder or neither substance use disorder.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Existing evidence suggests that worse neurocognitive performance and higher rates of impairment can result from methamphetamine use (Daldegan-Bueno et al, 2021;Naveed et al, 2022;Reback et al, 2018;Saloner et al, 2020;Scheffler et al, 2022;Watson et al, 2020), and our present results are consistent with these findings. Lifetime methamphetamine use disorder was associated with worse neurocognitive performance and higher rates of NCI, relative to lifetime cannabis use disorder or neither substance use disorder.…”
Section: Discussionsupporting
confidence: 92%
“…The connection between methamphetamine use and neurocognitive deficits has been well documented, with prominent deficits observed in episodic memory, executive functioning, information processing speed, and visuospatial abilities (Daldegan-Bueno et al, 2021; Naveed et al, 2022; Reback et al, 2018; Saloner et al, 2020; Scheffler et al, 2022; Watson et al, 2020). Research on cannabis use and neurocognitive outcomes is less conclusive than for methamphetamine use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some qualitative-based studies identified reports of cannabis being used as self-medication to alleviate crackcocaine detriments or cravings by populations with socioeconomic vulnerabilities. Related, there is a growing interest in cannabinoids as therapeutic agents for addiction treatment [150,151]; however, available data for psychostimulants (i.e., cocaine and amphetamines) are mostly preliminary and still inconclusive [152,153]. Overall, these reports call attention to the potential of cannabinoid product use to reduce the risk for harm from crack-cocaine use, especially in the Brazilian context of common crack-cocaine and/or amphetamine use by socio-economically marginalised groups [93,154].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence linking methamphetamine use to neurocognitive deficits is robust, with lower relative performance and greater rates of impairment being observed in memory, executive functioning, information-processing speed, and visuospatial abilities [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%